إستراتيجيات التدريس الحديثة المتبعة من طرف معلمي الإبتدائيات دراسة استكشافية ببعض إبتدائيات مدينة الأغواط - بعيط حميدة; العيهار دليلة; عياط الأمين (My University, 2019)
The study aimed to identify the most important teaching strategies and obstacles that face the primary stage teachers in the city of Laghouat. The students adopted the descriptive approach and a sample was chosen for the multi-stage study. The sample of the approved study was composed of 60 teachers and teachers in the primary stage. Two axes were formed: the first is related to modern teaching strategies, and the second is on the obstacles facing primary school teachers. The students applied the tool to the research sample after verifying its validity and stability. The most important results of the study were as follows: / The results of the half interview with the primary education teachers showed that the results of the interview were: - Most of the respondents received a composition on the teaching strategies. Most of the sample has knowledge of the theories of learning. - Different opinions of teachers on the method of teaching used by the teacher, where came first method of exploration and then the discussion followed by the method of play and brainstorming and in the final cooperative learning. - The available means are the basic criterion through which to choose the teaching strategy.- The majority allow students to choose their roles. - The majority share with the students in providing solutions to learning problems - Majority takes into account individual differences between learners in teaching. - School administration does not provide the conditions to activate the teaching strategy. - Few training courses on learning and teaching. - Most of the courses around the teaching strategies are superficial. Lack of time to apply modern teaching strategies. - The number of pupils in the largest impedes the implementation of these strategies. Experience is key to the success and implementation of this strategy The results of the study showed that the main obstacles faced by teachers of primary education in activating the teaching strategies are: lack of time and lack of means of learning and the large number of students in the classroom, in addition to the nature of the training received by teachers, which is mostly if not all theoretical composition and only.